Effects of Sophora alopecuroides L., Zingiber officinale Rosc. and Melissa officinalis L. in Formalin and Straub Tail Tests - S Kianbakht; R Hajiaghaee (Institue of Medicinal Plants, ACECR, 2014)
Background: S. alopecuroides, Z. officinale and M. officinalis are used traditionally in the treatment of pain. Objective: To evaluate the plants effects in the rat formalin test and their activity on the opioid receptors. Methods: Each rat was placed individually in a cage for 30 min to get acclimated. Then 0.05 mL of 10% formalin was injected subcutaneously into the dorsal surface of the right hind paw of the rat. Afterward, the animal was returned to the cage for observation. Pain responses were scored at 30 and 60 min after formalin injection. 90% ethanol extract was injected subcutaneously 30 min before formalin injection. To evaluate the role of opioid receptors in the analgesic effect of the extracts inhibiting the early phase of the test, naloxone was injected subcutaneously 30 min before extract injection. Moreover, the extracts effects on the Straub reaction were studied in mice. Mice were placed in individual cages immediately after extract injection for observation. The positive Straub tail response was considered as a persistent elevation of the tail at an angle more than 45º, 30 min after extract injection. Results: S. alopecuroides and M. officinalis inhibited both phases of the formalin test (p<0.05), but Z. officinale inhibited only the late phase (p<0.05). Naloxone did not reverse the effects of S. alopecuroides and M. officinalis in the formalin test. Further, the extracts did not cause Straub reaction. Conclusion: The plants have analgesic effect without opioid including µ2 receptor activity and may not produce the side effects caused by activation of µ2 receptors.